(untitled) (Czech Journal of Multidisciplinary Innovations, 2022)
Modern achievements of world medical science and practice have made it possible to achieve tremendous success in the treatment of chronic non-infectious diseases. Improving the prognosis and quality of life of people suffering from the most common socially significant pathology of the circulatory system – coronary heart disease (CHD), contributes to progressive aging of the population economically developed countries. Thus, the number of DM patients in the world over the past 10 years has increased more than 2 times and by the end of 2015 reached 415 million people. According to the forecasts of the International Diabetes Federation, 642 million people will suffer from diabetes by 2040. According to the Federal Register, in Russia in 2016, 4 million people were registered for DM2, which amounted to almost 3% population. However, these data underestimate the real number of patients, since they only take into account you-revealed and registered cases of the disease, and the real number of patients with DM in the Russian Federation can reach 8-9 million people (about 6% of the population). It was noted that in more than 60% of cases in patients with DM2 cardiovascular diseases develop, and they are the cause of death of most patients. It is known that the risk of acute heart attack myocardium in patients with DM2 is 6-10 times higher than in the general population. The combination of coronary heart disease and diabetes is one of the most unfavorable conditions and leads to a multiple increase in cardiovascular complications and mortality of patients. The problem of comorbidity of these two most widespread non- infectious pathologies is traditionally indicated mainly in the cohort of elderly and senile patients. However, recently the time recorded is "rejuvenation" of SD2. So, about 50% of all patients with DM2 in the world are aged 40-59 years old, i.e. people of active working age, which significantly aggravates the economic aspect of this problem